The association between lifelines diet score and metabolic associated fatty liver disease: a case–control study - Direksunthorn, Thanyaporn; Abdelgawwad El-Sehrawy, Amr Ali Mohamed; Hjazi, Ahmed; Obaidur Rab, Safia; Suliman Maashi, Marwah (Frontiers in Nutrition, 2025)
IntroductionAdherence to a healthy dietary pattern is a fundamental recommendation for the prevention of Metabolic Associated Fatty Liver Disease (MAFLD); however, conclusive evidence regarding the optimal dietary pattern remains elusive.ObjectivesThe Lifelines Diet Score (LLDS) is a novel, evidence-based scoring system designed to evaluate diet quality. However, despite the extensive research on dietary patterns and liver health, the specific relationship between the LLDS and MAFLD remains underexplored. This study aims to investigate the association between LLDS and MAFLD, providing insights into how dietary adherence, as measured by LLDS, may influence the risk and prevalence of MAFLD.MethodsThis case–control study enrolled 215 individuals who had recently been diagnosed with MAFLD and 430 healthy controls at King Khalid University Hospital. All participants were aged between 20 and 60 years, with data collection occurring from February 2023 to January 2025. The dietary intake of the participants was assessed through the utilization of a validated semi-quantitative food frequency questionnaire, which comprised a total of 168 distinct food items. Logistic regression was used to estimate the association between LLDS and MAFLD.ResultsOut of 645 participants, 215 newly diagnosed MAFLD patients and 430 healthy controls were analyzed. After stratifying participants based on LLDS tertiles, those in the highest LLDS group had a 78% lower odds of MAFLD than those in the lowest tertile (odds ratio (OR): 0.22; 95% Confidence interval (CI): 0.12–0.36, p for trend <0.001). The association remained robust even after adjustment for major confounders. These findings highlight a novel and robust association between LLDS and MAFLD, providing evidence for dietary pattern assessment in liver health research.ConclusionOur study strengthens the evidence that adherence to a healthy dietary pattern (as measured by LLDS) is associated with a lower MAFLD risk, even after accounting for major confounders. However, further research integrating genetic and molecular data is needed to refine personalized dietary recommendations for MAFLD prevention.